Shaping Learner Responses in Question-Answer Sequences in the EFL Classroom - Pouromid, Sajjad (International Journal of Learning, Teaching and Educational Research, 2019)
The construct of classroom interactional competence builds upon propositions made by the sociocultural theory of learning to explore the interactional consequences of teacher talk in the foreign language classroom. The sociocultural theory upholds learner participation as the key for learning to take place. Meanwhile, studies with a conversation analytic methodology have shown that learner participation depends in part on teachers’ interactional practices or their classroom interactional competence. That is, teacher talk has the potential to shape learner contributions in the classroom and either facilitate or obstruct their participation. The present study has investigated how teacher talk can do so across question-answer sequences in two EFL classes in Japan and Taiwan in a Collaborative Online International Learning program. The microanalytic study of question-answer sequences in the data indicated that while referential questions, as opposed to display questions, are more likely to generate more elaborate learner responses, the interactional context in which questions are posed can influence their outcome as well. Among the interactional practices identified as facilitators of learners’ participation were asking referential questions at TRPs, asking referential follow-up questions when a communicative breakdown emerges, teacher echoing of learner responses, and paraphrasing the referential question already asked. On the contrary, practices including self-elaboration, selfanswering, asking referential questions in or after extended teacher turns, teacher interruptions, and teacher turn completions were found to have obstructive effects on learners’ responses. https://doi.org/10.26803/ijlter.18.12.8